Mrs. Dalloway - Woolf, Virginia, 1882-1941. (Orlando, Fla. : Harcourt, 1981)
Depicts the events, thoughts, and actions of a single day in the life of Clarissa Dalloway.
Young Adult
Young Adult
New York Times
950
Keywords: Married women -- England -- Fiction; England -- Fiction; Wives -- England -- Fiction; England -- Fiction; Domestic fiction; Domestic fiction